GENRE SPECIFICS AND POETIC FEATURES OF SMALL GENRES IN UZBEK FOLKLORE - Shahnoza Toxirjonovna Rahimova (International Journal of Literature and Language Studies, 2026)
Abstract: This article is dedicated to the systematic study of the small genres of Uzbek folklore, which constitute an integral part of the spiritual and cultural heritage of the Uzbek people. Small folklore genres, including proverbs, riddles, sayings, quick-spoken words (tongue twisters), and lullabies, reflect the historical experience, ethical norms, and aesthetic ideals of the nation. The paper analyzes the structural-semantic characteristics, poetic principles, and pedagogical functions of these genres based on classical and modern folklore methodologies. By examining the classification frameworks established by prominent folklorists, the article demonstrates how small genres maintain high stability while adapting to changing socio-cultural environments. The research provides a comprehensive breakdown of the linguistic, artistic, and thematic boundaries that distinguish each sub-genre within the broader paradigm of oral traditions.